2012
DOI: 10.1093/nar/gks529
|View full text |Cite
|
Sign up to set email alerts
|

CPred: a web server for predicting viable circular permutations in proteins

Abstract: Circular permutation (CP) is a protein structural rearrangement phenomenon, through which nature allows structural homologs to have different locations of termini and thus varied activities, stabilities and functional properties. It can be applied in many fields of protein research and bioengineering. The limitation of applying CP lies in its technical complexity, high cost and uncertainty of the viability of the resulting protein variants. Not every position in a protein can be used to create a viable circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 44 publications
0
48
0
Order By: Relevance
“…In addition, we provide evidence that the tolerance of a thermophilic phosphotransferase to circular permutation correlates strongest with three parameters, including: (i) the distance between the backbone fission and AK phosphotransfer site, (ii) AK family sequence variability at residues near the fission site, and (iii) root mean square deviation (RMSD) of residues near the fission site in superimposed AK structures. Among the structure-derived metrics analyzed, these three structure-derived metrics correlated with functional conservation to the greatest extent, while no significant correlation was observed using CPred 27,28 .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, we provide evidence that the tolerance of a thermophilic phosphotransferase to circular permutation correlates strongest with three parameters, including: (i) the distance between the backbone fission and AK phosphotransfer site, (ii) AK family sequence variability at residues near the fission site, and (iii) root mean square deviation (RMSD) of residues near the fission site in superimposed AK structures. Among the structure-derived metrics analyzed, these three structure-derived metrics correlated with functional conservation to the greatest extent, while no significant correlation was observed using CPred 27,28 .…”
Section: Introductionmentioning
confidence: 84%
“…These studies have revealed that polypeptides involved in early folding events and stability display a low tolerance to backbone fission arising from permutation 8,9 . Structure-derived parameters extracted from these studies have been used to develop an algorithm (CP site predictor, CPred), which scores the likelihood that proteins fold and function upon circular permutation 27,28 . To date, the quality of CPred predictions has not been tested with a thermophilic protein, and it remains unclear how well CPred anticipates the results of a combinatorial experiment involving proteins with extreme stability.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement of in silico analysis into CP prediction helped in the selection of circular permutations in lichenase sequence [10,30,41]. New open termini in two CP lichenase variants (CN-53 and CN-99) had no effect on both the activity and thermal tolerance unlike another CP variant, CN-140, which displayed a dramatic decrease in the activity and thermostability, presumably associated with a loss in stability at a high temperature ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The circularly permutated lichenase homologs were searched for using iSARST web server [29] and the Blast software in PDB [26]. Potential CP sites in proteins were predicted using the CPred web server [30].…”
Section: In Silico Analysismentioning
confidence: 99%
See 1 more Smart Citation